Roles of Cullin-RING Ubiquitin Ligases in Cardiovascular Diseases - Stephanie Diaz; Kankan Wang; Benita Sjögren; Xing Liu (Biomolecules, 2022)
Maintenance of protein homeostasis is crucial for virtually every aspect of eukaryotic biology. The ubiquitin-proteasome system (UPS) represents a highly regulated quality control machinery that protects cells from a variety of stress conditions as well as toxic proteins. A large body of evidence has shown that UPS dysfunction contributes to the pathogenesis of cardiovascular diseases. This review highlights the latest findings regarding the physiological and pathological roles of cullin-RING ubiquitin ligases (CRLs), an essential player in the UPS, in the cardiovascular system. To inspire potential therapeutic invention, factors regulating CRL activities are also discussed.